Effects of antipsychotics on insight in schizophrenia: results from independent samples of first-episode and acutely relapsed patients. (July 2016) - Misiak, Błażej; Frydecka, Dorota; Beszłej, Jan A.; Moustafa, Ahmed A.; Tybura, Piotr; Kucharska-Mazur, Jolanta; Samochowiec, Agnieszka; Bieńkowski, Przemysław; Samochowiec, Jerzy
Abstract : We aimed to investigate whether antipsychotics differentially impact insight and whether these effects appear because of improvement in psychopathological manifestation in 132 first-episode schizophrenia patients and 201 acutely relapsed schizophrenic patients, who were followed up for 12 weeks. Olanzapine and risperidone were administered to first-episode schizophrenia patients, whereas acutely relapsed schizophrenic patients were treated with olanzapine, perazine and ziprasidone. The Positive And Negative Syndrome Scale (PANSS) was used to assess psychopathology. Insight was assessed using the G12 item of PANSS. Unadjusted mixed-model regression analysis indicated a significant improvement in the PANSS G12 item score in both groups. There were no significant differences between distinct treatment subgroups of patients in terms of improvement in the PANSS G12 item score. After adjustment for the trajectories of changes in symptom dimensions, a decrease in the PANSS G12 item score was because of an improvement in positive, negative and excitement symptoms. A decrease in the PANSS G12 item score was also related to an increase in the severity of depressive symptomatology. Our results indicate that antipsychotics exert similar effects on insight in acute psychosis. These effects are likely because of an improvement in psychopathological manifestation. The improvement in insight might be related to the development of depressive symptoms.